THE INFLUENCE OF TAX KNOWLEDGE AND TAX FAIRNESS ON VOLUNTARY TAX COMPLIANCE OF MOTOR VEHICLE TAXPAYERS IN DKI JAKARTA - Nurul Widyastari; Inayati Inayati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the effect of tax knowledge and perceptions of tax fairness on voluntary tax compliance among motor vehicle taxpayers in DKI Jakarta. The background of this study is based on the phenomenon of an increase in the number of motor vehicles that is not fully accompanied by an increase in compliance with Motor Vehicle Tax (PKB) payments, as reflected in high tax receivables and the dominance of vehicles with passive status. This study uses a quantitative approach with an explanatory survey design. Primary data were collected through the distribution of Likert scale questionnaires to motor vehicle taxpayers selected using purposive sampling techniques. Data analysis was performed using multiple linear regression to test the partial and simultaneous effects between variables. The results of the study are expected to show that tax knowledge and perceptions of tax fairness have a positive and significant effect on voluntary tax compliance. These findings are expected to contribute theoretically to the development of tax compliance literature and provide practical recommendations for local governments in formulating policies that encourage sustainable tax compliance.